2008
DOI: 10.1016/j.bone.2008.06.017
|View full text |Cite
|
Sign up to set email alerts
|

High molecular weight tropomyosins regulate osteoclast cytoskeletal morphology

Abstract: Tropomyosins are coiled-coil dimers that bind to the major groove of F-actin and regulate its accessibility to actin-modifying proteins. Although approximately 40 tropomyosin isoforms have been identified in mammals, they can broadly be classified into two groups based on protein size, that is, high molecular weight and low molecular weight isoforms. Osteoclasts, which undergo rounds of polarization and depolarization as they progress through the resorptive cycle, possess an unusual and highly dynamic actin cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Tpm1.6 and Tpm3.1 display diffuse localization throughout the interior of the cell, whereas Tpm4.2, Tpm1.8 and Tpm1.9 localize to actin-rich adhesion structures, such as the podosomes and the sealing zone (McMichael et al, 2006). RNA interference studies further demonstrated that Tpm1.6 contributes to osteoclast morphogenesis and motility, whereas Tpm4.2 is involved in assembly and/or maintenance of adhesion structures Kotadiya et al, 2008 Fig. 3.…”
Section: Role Of Tpm-containing Filaments In Cytoskeletal Structuresmentioning
confidence: 94%
“…Tpm1.6 and Tpm3.1 display diffuse localization throughout the interior of the cell, whereas Tpm4.2, Tpm1.8 and Tpm1.9 localize to actin-rich adhesion structures, such as the podosomes and the sealing zone (McMichael et al, 2006). RNA interference studies further demonstrated that Tpm1.6 contributes to osteoclast morphogenesis and motility, whereas Tpm4.2 is involved in assembly and/or maintenance of adhesion structures Kotadiya et al, 2008 Fig. 3.…”
Section: Role Of Tpm-containing Filaments In Cytoskeletal Structuresmentioning
confidence: 94%
“…Mature osteoclasts, as evidenced by a peripheral belt of podosomes (35), were present by days 5-7 of culture. Resorption and motility assays were performed as previously described (34,36).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were fixed and permeabilized, as previously described (28,33,34,36). Primary antibodies were added in a standard polyethylene glycol blocking buffer and were detected using Alexacoupled secondary antibodies (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…16,21,[77][78][79][80] In addition, overexpression studies complemented with targeted gene siRNA knockdown experiments have demonstrated the importance of specific Tm isoforms in regulating the structure and dynamic properties of focal adhesions. 76,81 Finally, recent siRNA knockdown experiments have played an important role in establishing the nonredundant roles of Tm isoforms in stress fiber assembly.…”
Section: 56mentioning
confidence: 99%